Analysis of the Influence of Using Learning Media in Increasing Students' Learning Motivation - Hasanah, Rifatun; Jumini, Sri (Indonesian Journal of Innovation in Education Research, 2025)
Education is a conscious effort made to develop students' potential and knowledge. Boring learning makes students uninterested in participating in learning activities, with learning media making teaching and learning activities fun. This study aims to measure the extent to which the use of learning media can affect students' motivation in learning in the current digital era. In today's rapid technological developments, learning media has become an important tool in the learning process. This study uses the literature review method with data sources used collected using the document study method, namely searching for sources from journals, articles, and e-books. The results of this study indicate that the use of learning media has a very significant influence on increasing students' motivation and interest in learning. With the development of technology, many learning media can be an option to be applied in the teaching and learning process. In this case, digital learning media has a positive impact on creating fun learning activities and can significantly increase students' learning motivation.